Anharmonic contribution to the stabilization of Mg(OH)2 from first principles. Issue 26 (20th June 2018) - Treviño, P.; Garcia-Castro, A. C.; López-Moreno, S.; Bautista-Hernández, A.; Bobocioiu, E.; Reynard, B.; Caracas, R.; Romero, A. H.
Abstract : Geometrical and vibrational characterization of magnesium hydroxide was performed using density functional theory. Abstract : Geometrical and vibrational characterization of magnesium hydroxide was performed using density functional theory. Four possible crystal symmetries were explored: P 3̄ (No. 147, point group −3), C 2/ m (No. 12, point group 2), P 3 m 1 (No. 156, point group 3 m ) and P 3̄ m 1 (No. 164, point group −3 m ) which are the currently accepted geometries found in the literature. While a lot of work has been performed on Mg(OH)2, in particular for the P 3̄ m 1 phase, there is still a debate on the observed ground state crystal structure and the anharmonic effects of the OH vibrations on the stabilization of the crystal structure. In particular, the stable positions of hydrogen are not yet defined precisely, which have implications in the crystal symmetry, the vibrational excitations, and the thermal stability. Previous work has assigned the P 3̄ m 1 polymorph as the low energy phase, but it has also proposed that hydrogens are disordered and they could move from their symmetric position in the P 3̄ m 1 structure towards P 3̄. In this paper, we examine the stability of the proposed phases by using different descriptors. We compare the XRD patterns with reported experimental results, and a fair agreement is found. While harmonic vibrational analysis shows that most phases have imaginary modes at 0 K, anharmonic vibrational analysis indicates that at room temperature only the C 2/ m phase is stabilized, whereas at higher temperatures, other phases become thermally competitive.